Active targeting of gold nanoparticles as cancer therapeutics - Goddard, Zoë Rachael; Marín, María J.; Russell, David A.; Searcey, Mark (Chemical Society reviews, 2020)
Gold nanoparticles (AuNPs) are of increasing interest for their unique properties and their biocompatability, minimal toxicity, multivalency and size tunability make them exciting drug carriers. The functionalisaton of AuNPs with targeting moieties allows for their selective delivery to cancers, with antibodies, proteins, peptides, aptamers, carbohydrates and small molecules all exploited. Here, we review the recent advances in targeted-AuNPs for the treatment of cancer, with a particular focus on these classes of targeting ligands. We highlight the benefits and potential drawbacks of each ligand class and propose directions in which the field could grow.